Collaboration of Actors (Government, Private, Community) in Handling Environmental Impacts from Waste Disposal by PT. Obsidian Stainless Steel - Rizky Ilhami; R. Taqwaty Firdausijah; M. Rizky Ganda Hutama; Tri Yoga Wibisono (CV. AFDIFAL MAJU BERKAH, 2024)
The environmental crisis is a phenomenon that occurs in various parts of the world. Environmental activists also highlight various issues related to environmental damage by campaigning for the public to understand how damaged the earth is as a result of the actions and negligence of irresponsible individuals and corporate groups. PT. Obsidian Stainless Steel, which is a leading company in Southeast Sulawesi, has recently violated the management and sustainability of natural resources. The impacts arising from waste disposed of haphazardly by PT. OSS have resulted in clean air being polluted, rice fields drying out, crop failure and worsening public health. For this reason, collaborative governance between government, citizens and other groups is needed which is expected to increase cooperation and good coordination in dealing with environmental issues, so as to create sustainable environmental conditions.